Where next for social prescribing in England?. Issue 5 (May 2018) - Ogden, Joy
Abstract : Social prescribing – the process of primary care professionals referring patients to a range of local non‐clinical services – was the focus of a conference organised by the Westminster Health Forum and held in London in March. Joy Ogden reports on some of the highlights of the conference.